O planejamento e o gerenciamento econômico-financeiros como instrumentos de redução da mortalidade das micro e pequenas empresas - estudo de caso: Restaurante Buongustaio - Santos, Valmir Cirilo dos (2001)
The present paper identifies the main causes of failures of small businesses in Brazil and points out the role of economic and financiai planning and management in the reduction of those failures. The paper focuses on the following elements mentioned in existing bibliography on small businesses: definitions, characteristics, importance, needs, principie difficulties of small enterprises, and rate of mortality of this sector of the economy. This study underscores the relevance of small businesses to society and the economy as a whole. The majority (98%) of enterprises is classified as a small businesses, which are responsible for 43% ofthe supply ofjobs and for almost half of all the revenue and production value in the country. Furthermore, this study examines research that shows that the failure rate of Brazilian enterprises is sizeable and worrying, reaching almost 60% during their first year of existence in some states. This phenomena can be attributed not to a single factor but to several causes - environmental, technical, administrative, among others - that can increase the risk of failure. However, research suggests that financiai issues are the main cause of failure for small businesses. The bibliography research indicates that the most urgent needs of small businesses are: better management and planning instruments, specialized training, cash flow, financing at rates compatible with revenue and professional management. XIT The mam source of research of the paper is the study of the creation, planning, management and administration of the Buongustaio restaurant in Brasília during its first ten months in operation. The restaurant' s main difficulties were examined, as well as creative solutions involving planning, management, human resources, cash flow, interaction with c1ients, among other issues. This case study employs concepts and ideas mentioned in the bibliography and concludes that the use of economic and financiaI planning and management instruments such as business plans, economic and financiaI analysis, cash flow management, can contribute positively towards the survival and growth of small businesses, reducing the rate of premature failures.